Progress in Industrial Mathematics at ECMI 2010 - Günther, Michael; Bartel, Andreas; Brunk, Markus; Schöps, Sebastian; Striebel, Michael; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
ECMI, the European Consortium for Mathematics in Industry, is the European brand associated with applied mathematics for industry and organizes highly successful biannual conferences. In this series, the ECMI 2010, the 16th European Conference on Mathematics for Industry, was held in the historic city hall of Wuppertal in Germany. It covered the mathematics of a wide range of applications and methods, from circuit and electromagnetic device simulation to model order reduction for chip design, uncertainties and stochastics, production, fluids, life and environmental sciences, and dedicated and versatile methods. These proceedings of ECMI 2010 emphasize mathematics as an innovation enabler for industry and business, and as an absolutely essential pre-requiste for Europe on its way to becoming the leading knowledge-based economy in the world.
Part I Circuit and Electromagnetic Device Simulation -- Part II Model Order Reduction for Chip Design -- Part III Uncertainties and Stochastics -- Part IV Production -- Part VI Life and Environmental Sciences -- Part VII Dedicated and Versatile Methods -- Index.
Keywords: Applied mathematics; Engineering mathematics; Mathematical optimization; Differential equations; Economics, Mathematical .; Partial differential equations; Computer mathematics; Applications of Mathematics; Optimization; Ordinary Differential Equations; Quantitative Finance; Partial Differential Equations; Computational Mathematics and Numerical Analysis